USE OF THE TALAQQI METHOD TO ACCELERATE AL-QUR'AN READING AT AL-AHZAB TPA - Nurbayani; Realita, Amiruddin; Lukman Affandi; Listri Anisa (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research aims to find out (1) How high is the fluency in pronunciation of the letters of the Qur'an through the talaqqi method at Al-Ahbab TPA, Cipare-pare Village, Sultan Daulat District, Subussalam City. (2) Is there an effect of using the talaqqi method in speeding up the reading of the Al-Qur'an at TPA? The application of the talaqqi method on fluency in reading the letters of the Al- Qur'an at TPA Al-Ahbab. The research method used in this research is quantitative research with an experimental approach. Researchers used the pre-experimental design method with a one-group pretest-posttest design. The population in this study were all students at the Al-Ahbab Al-Qur'an Education Park, totaling 26 students, while the sample was 15 students who were studying the Al-Qur'an class. The instrument used in research is a test. The test results after testing normality, homogeneity and hypothesis with the help of the SPSS 16 program found that the average value obtained was 60.40, while the average posttest value was 83.26, so an N-gain was obtained of 0.6, meaning that this experimental class experienced an increase. The result is at value (12.980), and a significant (2- tailed) value of 0.000 <0.05, so that H1 is accepted, and H0 is rejected. There is a difference in the learning achievement of students between the application of the talaqqi method and the application of the previous method in learning to read the letters of the Koran. There is a significant influence of applying the talaqqi method on fluency in reading the letters of the Koran at Al-Ahbab TPA. Thus, the application of the talaqqi method to improve fluency in reading the letters of the Koran at the Al-Ahbab Al-Qur'an Education Park shows better results compared to not using the talaqqi method.